Proposal and Validation of a Scale of Composite Measure Reactivity Score to Characterize the Reactivity in Horses During Handling - Calviello, Raquel Ferrari; Lencioni Titto, Evaldo Antonio; Infante, Paulo; Cunha Leme-dos-Santos, Thays Mayra da; Neto, Marcos Chiquitelli [UNESP]; Franco Pereira, Alfredo Manuel; Titto, Cristiane Goncalves (Elsevier B.V., 2016)
This study aimed to identify the parameters related to the expression of the reactivity in horses during handling and based on that proposed and validated a scale of composite measure reactivity score to characterize horse's reactivity. To this end, the first stage (S1) proposed the scale and the second (S2) validated it. In Sl, 364 Lusitano horses were evaluated, 188 were adult breeding mares (4-12 years old), and 176 were foals (males/ females, aged from 2 months to 2 years). During hooves trimming, vermifuge application, palpation scores were assigned to behaviors of movement, ears and eyes position, breathing, vocalization, and urination. A response parameter called reactivity was attributed to each animal, ranging from score 1 (nonreactive/calm) to score 4 (very reactive/aggressive). The verification of the possible parameters (age, behavior), which explains the response parameter (reactivity), was taken using ordinal proportional odds model. Movement, breathing, ears and eyes position, vocalization, and age appear to explain the reactivity of horses during handling (P <.01). Therefore, based on these parameters, it was possible to propose two scales of composite measure reactivity score: one to characterize the mares and another the foals. On S2, the proposed scale was validated by the simultaneous application of Forced Human Approach Test, another commonly used test to evaluate the reactivity in horses, with a correlation of 0.97 (P <.05). The assessment of the reactivity of horses during handling by a composite measure reactivity score scale is valid, and easy to apply, without disrupting daily routine and override the impact of individual differences. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Foal; Mare; Score of behavior; Temperament